Clinical and research applications of magnetic resonance imaging in the study of CADASIL. (17th April 2019) - Schoemaker, Dorothee; Quiroz, Yakeel T.; Torrico-Teave, Heirangi; Arboleda-Velasquez, Joseph F.
Highlights: MRI plays a central role in the clinical diagnosis of CADASIL. CADASIL shares similar MRI characteristics with other forms of cerebral small-vessel diseases. The imaging features of CADASIL vary across subjects and some evidence suggest that they may be influenced by genotype. At present, no MRI marker is sufficiently sensitive and specific to fully support the differential diagnosis of CADASIL. In the literature, lacunes and brain atrophy have been robustly related to disability and cognitive status in CADASIL. Abstract: Cerebral Autosomal Dominant Arteriopathy with Subcortical Infarcts and Leukoencephalopathy (CADASIL) is an inherited small vessel disease that leads to early cerebrovascular events and functional disability. It is the most common single-gene disorder leading to stroke. Magnetic resonance imaging (MRI) is a central component of the diagnosis and monitoring of CADASIL. Here we provide a descriptive review of the literature on three important aspects pertaining to the use of MRI in CADASIL. First, we review past research exploring MRI markers for this disease. Secondly, we describe results from studies investigating associations between neuroimaging abnormalities and neuropathology in CADASIL. Finally, we discuss previous findings relating MRI markers to clinical symptoms. This review thus provides a summary of the current state of knowledge regarding the use of MRI in CADASIL as well as suggestions for future research.